Social Stigmatisation among Tuberculosis Patients and Community People in Bangladesh: An Exploratory Study - Goutam K. Dutta; Md. Mostafizur Rahman; Dipika S. Bhattacharyya; Md. Musfikur Rahman; Palash K. Dey; Mosa E. Nur; Kazi Robiul Alom (Preventive Medicine: Research & Reviews)
Introduction: This study aims to investigate social perceptions and prejudice towards tuberculosis (TB) in Bangladesh and how these perceptions and prejudice contribute to retain social stigma among patients and community people. Materials and Methods: Authors employed phenomenological approach and conducted 20 in-depth interviews with TB patients and their caregivers at the hospital, using maximum variation purposive sampling to capture a wide range of perspectives and contexts. Results: Thematic analysis revealed that many participants believed societal misperception and prejudices fuel the stigmatisation of TB. Furthermore, misconceptions about the disease’s incurability were widespread, with non-infected participants expressing reluctance to interact with TB patients. In addition, findings indicated that patients often faced isolation from family and society due to stigma. Conclusion: These insights underscore the need for culturally sensitive interventions to bridge healthcare gaps and enhance community awareness about TB and its impact in Bangladesh.